Histamine-modulated wettability switching in G-protein-coupled receptor inspired nanochannel for potential drug screening and biosensing - Qi Zhao; Xu-Qin Ran; Zhu-Ying Yan; Hai-Long Qian; Xiu-Ping Yan (Nature Communications, 2025)
Abstract Histamine receptor, one typical G-protein-coupled receptor (GPCR), can be activated by histamine and form the most important drug targets involved in allergy and reflux diseases. Here, we report an artificial model to mimic the wettability-induced activation of natural GPCRs via histamine-modulated enhancement of wettability in a bionic nanochannel. The artificial receptor is constructed by introducing key recognition factors in nature, L-lysine modified fluorescein isothiocyanate (L-lysine-FITC), into a conical nanochannel. The conductance of the L-lysine-FITC-modified nanochannel increases with the histamine-induced wettability enhancement due to the various interactions between histamine and L-lysine-FITC molecules including hydrogen bonding and π-π interactions, as well as the proton transfer reaction. This study represents a crucial step towards the design of artificial GPCRs with wettability-induced activation and provides an opportunity to construct artificial models of GPCRs in a non-lipid environment. The developed artificial receptor has great potential application in medicinal chemistry, biosensors, and healthcare systems.